2007
DOI: 10.1071/ah070150
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay benchmarking in the Australian private hospital sector

Abstract: Length of stay (LOS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Likewise, for the ALOS indicator the consensus exercise suggested that a conservative approach keeping the benchmark and the minimum effort equivalent because of limits on case mix adjustment around ALOS. This is a conservative approach given that different authors have used more aggressive approaches [21,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, for the ALOS indicator the consensus exercise suggested that a conservative approach keeping the benchmark and the minimum effort equivalent because of limits on case mix adjustment around ALOS. This is a conservative approach given that different authors have used more aggressive approaches [21,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Using a sample of government-owned hospitals in Taiwan, Chang (1998) used DEA with regression analysis and reported that the scope of services provided and the proportion of veterans served are negatively and significantly associated with efficiency. More recent studies use more sophisticated techniques to improve efficiency measures by: comparing the relative efficiency of religious non-profit hospitals (Harrison and Sexton 2006); measuring efficiency in the presence of stochastic demand for hospital services (Smet 2007); and using length of stay benchmarking to measure efficiency (Hanning 2007).…”
Section: Performance Researchmentioning
confidence: 99%
“…The literature on performance measurement indicates that there are broad research perspectives on the factors that affect performance outcomes and the methodologies that can be used to measure these relationships (Hanning 2007;Updaw 1987). A selected overview of key papers on performance research in health care is presented in Table 4.…”
Section: Performance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed that duration of hospital stay is regarded as an indicator of efficiency. [1][2][3][4] For low dependency inpatients, a long hospital stay may imply ineffective treatment, which increases healthcare expenditure. Theoretically, reducing duration of stay may increase the capacity of available hospital beds and the admissions of new inpatients.…”
Section: Introductionmentioning
confidence: 99%